Effect of Telemonitoring on Moderate and Severe Exacerbations in Patients with COPD: Pooled Analysis of Two Randomized Controlled Trials in Denmark - Hyldgaard C; Ringbæk T; Andersen FD; Hansen EF; Jensen MS; Fenger-Grøn M; Trolle C; Ulrik CS (International Journal of COPD)
Charlotte Hyldgaard,1,2 Thomas Ringbæk,3 Frank Dyekjær Andersen,1 Ejvind Frausing Hansen,4 Michael Skov Jensen,1 Morten Fenger-Grøn,1 Christian Trolle,1,2 Charlotte Suppli Ulrik4,5 1Medical Diagnostic Center, University Clinic for Innovative Patient Pathways, Regional Hospital Central Jutland, Silkeborg/Viborg, Denmark; 2Department of Clinical Medicine, Aarhus University, Aarhus, Denmark; 3Allergy and Lung Clinic, Helsingør, Denmark; 4Respiratory Research Unit and Department of Respiratory Medicine, Copenhagen University Hospital- Hvidovre, Hvidovre, Denmark; 5Institute for Clinical Medicine, University of Copenhagen, Copenhagen, DenmarkCorrespondence: Charlotte Hyldgaard, Medical Diagnostic Center, University Clinic for Innovative Patient Pathways, Regional Hospital Central Jutland, Falkevej 1-3, Silkeborg, 8600, Denmark, Email chahyl@rm.dkBackground: Acute exacerbations of chronic obstructive pulmonary disease (AECOPD) are serious events with high morbidity and mortality. Previous studies investigated telemonitoring as a tool for prevention of hospitalizations with ambiguous results. The aim of the present study was to combine data from two randomized controlled trials conducted in Denmark in similar healthcare settings to explore number of hospitalizations for COPD, days of admission, and exacerbations treated outside hospitals.Methods: Recruitment took place during hospitalization for AECOPD and from outpatient COPD clinics. Patients were equally randomized to telemonitoring (N=251) in addition to usual care for six months or usual care alone (N=252). We used a negative binomial regression model with between-group comparisons expressed as incidence rate ratios (IRRs) for assessment of hospitalizations, admission days and moderate exacerbations and Kaplan-Meier time-to-event analysis for assessment of time to first COPD hospitalization.Results: No significant differences between the two studies were identified. In combined analyses, numerically fewer hospitalizations (IRR 0.85, 95% CI 0.62– 1.17) and hospitalization days (IRR 0.72, 95% CI 0.42– 1.23) were seen in the telemonitoring group, but the findings did not reach statistical significance whereas treatment for moderate exacerbations was significantly more frequent in the telemonitoring group (IRR 1.91, 95% CI 1.49– 2.45).Conclusion: No effect of telemonitoring on hospitalizations for AECOPD was documented in this large cohort of patients with severe COPD. However, the telemonitoring group received significantly more treatment for moderate exacerbations. This risk of overtreatment should be considered when telemonitoring is used in the care of patients with COPD.Keywords: chronic obstructive pulmonary disease, telemonitoring, exacerbations, hospitalization